The redox-dependent regulation of satellite cells following aseptic muscle trauma (SpEED): study protocol for a randomized controlled trial - Konstantinos Papanikolaou; Dimitrios Draganidis; Athanasios Chatzinikolaou; Vassiliki C. Laschou; Kalliopi Georgakouli; Panagiotis Tsimeas; Alexios Batrakoulis; Chariklia K. Deli; Athanasios Z. Jamurtas; Ioannis G. Fatouros (Trials, 2019)
Abstract Background Muscle satellite cells (SCs) are crucial for muscle regeneration following muscle trauma. Acute skeletal muscle damage results in inflammation and the production of reactive oxygen species (ROS) which may be implicated in SCs activation. Protection of these cells from oxidative damage is essential to ensure sufficient muscle regeneration. The aim of this study is to determine whether SCs activity under conditions of aseptic skeletal muscle trauma induced by exercise is redox-dependent. Methods/design Based on the SCs content in their vastus lateralis skeletal muscle, participants will be classified as either high or low respondents. In a randomized, double-blind, crossover, repeated-measures design, participants will then receive either placebo or N-acetylcysteine (alters redox potential in muscle) during a preliminary 7-day loading phase, and for eight consecutive days following a single bout of intense muscle-damaging exercise. In both trials, blood samples and muscle biopsies will be collected, and muscle performance and soreness will be measured at baseline, pre-exercise, 2 and 8 days post exercise. Biological samples will be analyzed for redox status and SCs activity. Between trials, a 4-week washout period will be implemented. Discussion This study is designed to investigate the impact of redox status on SCs mobilization and thus skeletal muscle potential for regeneration under conditions of aseptic inflammation induced by exercise. Findings of this trial should provide insight into (1) molecular pathways involved in SCs recruitment and muscle healing under conditions of aseptic skeletal muscle trauma present in numerous catabolic conditions and (2) whether skeletal muscle’s potential for regeneration depends on its basal SCs content. Trial registration ClinicalTrials.gov, ID: NCT03711838. Registered on 19 Oct 2018.